1986
DOI: 10.1073/pnas.83.3.576
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of a thermostable enzyme variant by cloning and selection in a thermophile.

Abstract: We developed a method for rapidly generating thermostable enzyme variants. Our strategy is to introduce the gene coding for a given enzyme from a mesophilic organism into a thermophile, Bacillus stearothermophilus. Variants that retain the enzymatic activity at the higher growth temperatures of the thermophile are then selected. This strategy was applied to kanamycin nucleotidyltransferase, which confers resistance to the antibiotic kanamycin. B. stearothermophilus carrying the wild-type enzyme is resistant to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
117
0

Year Published

1993
1993
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 240 publications
(117 citation statements)
references
References 27 publications
0
117
0
Order By: Relevance
“…A variety of studies [27][28][29][30][31] have shown that the majority of point mutations have little effect on stability. For example, of over 2000 mutations made to T4 lysozyme, 91 % had no significant effect on thermal stability [24,25].…”
Section: Conformational Stability Of Enzymesmentioning
confidence: 99%
See 1 more Smart Citation
“…A variety of studies [27][28][29][30][31] have shown that the majority of point mutations have little effect on stability. For example, of over 2000 mutations made to T4 lysozyme, 91 % had no significant effect on thermal stability [24,25].…”
Section: Conformational Stability Of Enzymesmentioning
confidence: 99%
“…However, for those mutations that alter stability, destabilization is a more common effect. For a number of enzymes where enough data have been gathered [28][29][30][31], including lysozyme [28] and subtilisin [31], the occurrence of random point mutations which cause stabilization is of the order of 1 in 10 000. The destabilizing mutations in lysozyme (about 9 % of the total) all occurred at amino acids which have restricted mobility [24,25,32].…”
Section: Conformational Stability Of Enzymesmentioning
confidence: 99%
“…Ampli¢ed fragment was digested with SphI and EcoRI and ligated with pUC18 previously digested with the same enzymes. Resulting plasmid named pDFRE was digested with Aor51HI, treated with calf intestine alkaline phosphatase, and ligated with blunt-ended HindIII fragment of pUC39-442KmR [13] that contains heat-stabilized kanamycin nucleotidyltransferase gene [14]. The resulting plasmid was named pDFREKmR and used for knockout of the lysK gene of T. thermophilus HB27 as described previously [7].…”
Section: Cloning Of the Downstream Region Of Lysj Genementioning
confidence: 99%
“…Methods to identify thermostable variants have previously been developed for kanamycin nucleotidyltransferase (Matsumuratk Aiba, 1985;Liao et al, 1986), subtilisin (Bryan et al, 1986), and glucose dehydrogenase (Makino et al, 1989).…”
mentioning
confidence: 99%